50 A multi-professional educational intervention to improve and sustain respondents' confidence to deliver palliative care: a mixed methods study. Issue 3 (1st September 2017) - Reed, Elizabeth; Todd, Jennifer; Sadler, Clair; Berg, Jane; Lucas, Caroline; Lawton, Sally; Grant, Robert; Watson, Max
Abstract : Background: Education has been highlighted as fundamental in equipping healthcare professionals with essential knowledge and skills to provide good end of life care. Multiprofessional educational programmes have a positive influence on knowledge, attitude and confidence but few explore the longer term impact on care delivery. The educational intervention we evaluated is an eight week home-study based programme for healthcare professionals and is currently run in nine European centres. Aims: To evaluate the impact the educational intervention has on participants' confidence in palliative care, to determine if this is sustained over time. Design: A mixed method longitudinal approach Setting/participants: A survey using a self-efficacy scale was emailed to 342 candidates who undertook the educational intervention and semi-structured interviews to a sub-sample of 15 candidates at baseline, 3 and 6 months. Results: At three months, candidates had twenty times higher odds of being above any given level of confidence than baseline which was sustained at six months. Confidence was expressed in terms of communication clinical practice and multiprofessional working. Conclusion: Findings suggest the ECEPC improves confidence in palliative care that is sustained over time with evidence of confidence in symptom control, communication and a holistic approach in clinical practice.